Two experimental instruments inspired by radio technologies - Koutsomichalis, Marinos (My University, 2024)
This short paper accounts for (a) a wearable radio receiver that can be operated in the fashion of a monochord string instrument, and (b) for a rotating induction coil. Technical aspects are discussed and the process is exposed as laboratory experimentation with radio technologies.